Strategi Program Melalui Penghadiran Kedekatan Dengan Penonton (Studi Kasus Episode â€œMisteri Pesona Sindenâ€) - Kurniawan, Donie Fadjar; Pradita, Ahmad Iran (Capture : Jurnal Seni Media Rekam, 2014)
Opera Van Java is a television comedy drama show that the idea of the show isin the form of modern puppet show. It is said to be modern because the story is generallydeveloped from stories emerging in society. Opera Van Java is a comedy drama full ofartistic-arrangement elements that support the storyline in each episode. Statement ofthe problem in this research is how the setting, makeup and costume drama televisioncomedy Opera Van Java as a programming strategy through presenting closeness withthe audience. The purpose of this study is to describe how the setting, makeup andcostume of television comedy drama Opera Van Java as a programming strategy throughpresenting closeness with the audience. This study used a qualitative descriptive methodand its sample selection using purposive sampling technique. The selected sample wasepisode â€œMisteri Pesona Sindenâ€. The selection of episodes based on the local contentthat can be described and analyzed further. The results of the analysis on an episode ofthe television comedy drama â€œMisteriPesonaSindenâ€ are artistic-arrangement elementslike setting, make up and costumes shown in things and objects are often seen, perceivedand used in everyday society. In the end, the fact is then able to present and bringcloseness with the studio audience and viewers at home.Keywords: setting, makeup, costume, Opera Van Java, Misteri Pesona Sinden